The Graduate Employability Indicators: capturing broader stakeholder perspectives on the achievement and importance of employability attributes. - Oliver, Beverley; Hunt, L.; Jones, S.; Pearce, A.; Hammer, S.; Jones, Sue; Whelan, Barbara (Australian Universities Quality Agency, 2010)
With an increasing focus on academic standards, quality and graduate employability outcomes, Australian Higher Education institutions have a greater need to develop and utilise feedback mechanisms to assess and improve graduate employability outcomes. This paper reports on the development of the Graduate Employability Indicators (GEI), a suite of surveys for graduates, employers and members of the course teaching team on the importance of 14 employment capabilities for graduate workplace success and their demonstration by new graduates up to five years out. These surveys have been developed through an ALTC grant, Building course team capacity for graduate employability, a collaborative project between Curtin University, RMIT University, University of Southern Queensland and Victoria University. The paper outlines the similarities and differences between the GEI and other indicators, such as the Australian Graduate Pathways Survey (GPS), the Australasian Survey of Student Engagement (AUSSE) and the National Survey of Student Engagement (NSSE), demonstrating its potential use in national and international benchmarking activities. Summary visual data on the perspectives of graduates from one of the pilot surveys is also provided to demonstrate the type of information that can be gleaned from the surveys.